2022
DOI: 10.3389/fpsyt.2022.877460
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain-Health Related Modifiable Risk Factors in Older Adults After One Year of COVID-19-Restrictions

Abstract: BackgroundThe COVID-19 pandemic has major influence on lifestyle and mental health, which might affect brain-health and increase the risk of cognitive decline, particularly in older adults. We aimed to describe changes in modifiable risk factors related to brain-health in older adults after one year of COVID-19 restrictions.MethodsAn online survey was disseminated between February and March 2021 to 17,773 registrants of the Dutch Brain Research Registry, aged ≥50, without a self-reported diagnosis of mild cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…During NREM sleep, acquired information is reactivated and integrated into long-term memory, which is stabilized by a synaptic consolidation process during REM sleep 53 . Furthermore, higher frequency of sleep disorders and impaired sleep quality in relation to pandemic was observed with the same survey in the United Kingdom in 37% of the responders 20 , so the increase in sleep problems seems to be general across the various geographical regions.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…During NREM sleep, acquired information is reactivated and integrated into long-term memory, which is stabilized by a synaptic consolidation process during REM sleep 53 . Furthermore, higher frequency of sleep disorders and impaired sleep quality in relation to pandemic was observed with the same survey in the United Kingdom in 37% of the responders 20 , so the increase in sleep problems seems to be general across the various geographical regions.…”
Section: Discussionmentioning
confidence: 63%
“…The survey focused on changes in lifestyle factors, management of chronic noncommunicable diseases, as well as psychosocial factors, all of which are relevant to cognition and are expected to be affected by the pandemic. Local results in some countries are already available 18 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Another detrimental impact consistent with previous research is reduced physical activity levels during home confinement ( 28 , 37 ). The reductions on all levels of physical activity and greater amounts of time sitting daily ( 39 ) is described in several cross-sectional studies in Dutch, Japanese, Italian and Australian older adult samples ( 32 , 33 , 40 , 41 ). Our study expands on this and provides insights into the personal challenges involved in adapting and managing their lifestyles to foster physical activity under these new circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to brain health, Waterink and colleagues ( 32 ) found that 74% of participants reported at least one adverse lifestyle change, however, 60% of participants also reported at least one positive change including increased exercise, healthier food consumption and reduced alcohol consumption. These behaviors also differed based on sociodemographic factors such as age, gender, living circumstances, and income.…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown und Quarantäne, Veränderungen der Arbeitsbedingungen, wirtschaftliche Probleme und soziale Isolation lassen befürchten, dass sich die ohnehin nicht ausreichende Kontrolle von kardiovaskulären Risikofaktoren, zumindest bei einem Teil der Bevölkerung, weiter verschlechtert haben könnte. Auf der anderen Seite sind auch positive Effekte der Pandemie auf Präventionsmaßnahmen denkbar 17 18 19 20 . So könnte der Lockdown bei einigen Personen zu weniger Stress und mehr Zeit für Sport geführt haben.…”
Section: Diskussionunclassified